How the fluctuations of water levels affect populations of invasive bivalve Corbicula fluminea (Muller, 1774) in a Neotropical reservoir? - Paschoal, Lucas Rezende Penido [UNESP]; Andrade, Douglas de Pádua; Darrigran, Gustavo (Int Inst Ecology, 2015)
Corbicula fluminea is an invasive bivalve responsible for several environmental and financial problems around the globe. Despite the invasive potential of this species, it suffers certain restrictions in lentic environments due to natural phenomena that significantly affect its population structure (e.g. water column fluctuation and sunlight exposure). The present study addresses how temporal decline of the water level in a Neotropical reservoir and exposure to sunlight affect the population structure of C. fluminea. Samplings were carried out twice in the reservoir of Furnas Hydroelectric Power Station (HPS) (Minas Gerais, Brazil), in 2011 and 2012. Population density, spatial distribution and mean shell length of C. fluminea were estimated for each year after sampling in 51 quadrats (0.0625m(2)) placed on three transects at different distances along the reservoir margins (0, 10 and 20 m from a fixed-point). We observed a predominance of C. fluminea in both years, with a simultaneous gradual decrease in density and richness of native species in the sampling area. Significant differences in density of C. fluminea were registered at different distances from the margin, and are related to the temporal variability of physical conditions of the sediment and water in these environments. We also registered a trend toward an increase in the density and aggregation of C. fluminea as we moved away from the margin, due to the greater stability of these areas (>10 m). The mean shell length of C. fluminea showed significant difference between the distinct distances from the margin and during the years, as well as the interaction of these factors (Distances vs. Years). These results were associated with the reproductive and invasive capacity of this species. This study reveals that these temporal events (especially water column fluctuation) may cause alterations in density, spatial distribution and mean shell length of C. fluminea and the composition of the native malacofauna in Neotropical lentic environments.

Corbicula fluminea é um bivalve invasor, responsável por inúmeros problemas ambientais e econômicos ao redor do mundo. Apesar de sua capacidade de invasão, a espécie sofre certas restrições devido a fenômenos naturais em ambientes lênticos, afetando significativamente sua estrutura populacional (e.g. flutuação do nível da água e a exposição à luz solar). O presente trabalho avaliou como o decréscimo temporal do nível da água de um reservatório neotropical e a exposição solar, afeta a estrutura populacional de C. fluminea. Duas amostragens foram realizadas no reservatório da Usina Hidrelétrica (UHE) de Furnas (Minas Gerais, Brasil), em 2011 e 2012. A densidade populacional, o comprimento médio e a distribuição espacial da espécie para cada ano foram estimados após amostragem em 51 quadrats (0,0625m2 ) dispostos em três transectos em diferentes distâncias das margens do reservatório (0, 10 e 20 m em relação a um ponto fixo). Observou-se o predomínio de C. fluminea em ambos os anos, coincidindo com o decréscimo da densidade e riqueza de espécies nativas nas áreas de amostragem. Foram registradas diferenças significativas na densidade de C. fluminea entre as distâncias da margem, sendo atribuídas principalmente à variabilidade temporal do substrato e da água desses ambientes. Registrou-se também uma tendência em aumento da densidade e agregação com o aumento da distância da margem, devido à maior estabilidade dessas áreas (>10 m). Houveram diferenças significativas no tamanho médio das conchas de C. fluminea entre às distâncias da margem e durante os anos, assim como na interação desses fatores (Distâncias vs. Anos). Tais resultados foram associados à capacidade reprodutiva e invasiva da espécie. Esse estudo revelou que eventos temporais (principalmente, a flutuação do nível da água) em ambientes lênticos neotropicais provocam alterações na densidade, tamanho médio e distribuição de C. fluminea e na composição da malacofauna nativa.
Como a flutuação dos níveis da água afetam as populações do bivalve invasor Corbicula fluminea (Müller, 1774) em um reservatório neotropical?
Keywords: Non-native species; Desiccation; Water column levels; Ecological aspects; Furnas HPS reservoir; Espécie não-nativa; Dessecação; Nível da coluna de água; Aspectos ecológicos; Reservatório UHE Furnas